Strange Fruit - Moffett, Helen (Book collections on Project MUSE., 2009)
Strange Fruit is a courageous debut with a remarkable range in theme and tone, from the nostalgic to the comedic to the bawdy, and to the angry, the melancholic and the steadfast and comforting. It will delight, shock, anger, induce laughter, shock more, delight more. And make you blush. It's a full range. There are poems of brutally honest self-scrutiny - the heart of the collection being a series of poems on the ageing body, loss of love and infertility - and there are poems that capture landscapes with imagist skill and the botanist's detail.